(untitled) (Bangladesh Journal of Botany, 2021)
Stachys ahmet-savranii Doğu & Bağcı sp. nov. (Lamiaceae) from the Niğde (C5 Niğde, Turkey) is described and illustrated. It exhibits general features of the section Infrarosularis. It is closely related to Stachys citrina Boiss. & Heldr. but differs by its slender and unbranched stem; leaves structure; floral leaves equalling or longer than verticillasters; verticillester with 8 - 12 flowered and corolla 10 - 18 mm; Bracteoles reaching nearly middle of calyx tube. Diagnostic morphological characters are discussed. The geographical distribution of the new species is mapped. Notes are also presented on its ecology, biogeography and conservation status. Bangladesh J. Bot. 50(2): 319-326, 2021 (June)